Elevated proximal tibial strains following unicompartmental knee replacement—A possible cause of pain - Simpson, DJ; Price, AJ; Gulati, A; Murray, DW; Gill, HS (Elsevier, 2009)
Unexplained pain is an important complication of both total knee replacement and unicompartmental knee replacement. After unicompartmental knee replacement the most common site for the pain is antero-medial over the proximal tibia. The reason for this is not clear; however it may be due to high bone strain.